Peningkatan Literasi Digital dan Etika Bermedia Sosial bagi Santri Pondok Pesantren Nurul Qur’an Sebagai Wujud Tanggung Jawab Warga Negara Muda - Ayang Afira Anugerahayu; Muhammad Rifaldi Setiawan; Nathania Permata S; Ika Yuliana Susilawati; Ade Sultan Muhammad; Ahwan (BALE LITERASI, 2026)
The rapid development of information technology has made social media a dominant communication instrument, yet it also harbors serious risks such as the spread of hoaxes, hate speech, and privacy violations. This community service aims to enhance digital literacy and understanding of social media ethics among students (santri) at the Nurul Qur'an Islamic Boarding School as a form of responsibility for young citizens. The method employed is educational counseling, which includes lecture sessions, interactive discussions, and oral evaluations regarding the legal aspects of the Information and Electronic Transactions Law (UU ITE), digital safety, and social responsibility. The results show an increase in the students' awareness of critically filtering information and maintaining a positive digital footprint. With an evaluation success rate reaching >80%, this activity has successfully established the understanding that wise behavior in the virtual world is a concrete manifestation of civic values and an effort to maintain national integrity in the digital era. It is expected that the students will become agents of change who promote a healthy, safe, and productive digital environment.